Epidemiology and outcome of invasive fungal infections and methicillin-resistant Staphylococcus aureus (MRSA) pneumonia and complicated skin and soft tissue infections (cSSTI) in Lebanon and Saudi Arabia. Issue 6 (November 2017) - Moghnieh, Rima; Alothman, Adel F.; Althaqafi, Abdulhakeem O.; Matar, Madonna J.; Alenazi, Thamer H.; Farahat, Fayassal; Corman, Shelby L.; Solem, Caitlyn T.; Raghubir, Nirvana; Macahilig, Cynthia; Stephens, Jennifer M.
Abstract: The objectives of this retrospective medical chart review study were to document the inpatient incidence, treatment, and clinical outcomes associated with invasive fungal infections (IFI) due to Candida and Aspergillus species, Methicillin-resistant Staphylococcus aureus (MRSA) pneumonia and MRSA complicated skin and soft tissue infections (cSSTI) in the Middle East. This study evaluated 2011–2012 data from 5 hospitals in Saudi Arabia and Lebanon with a combined total of 207, 498 discharges. Hospital medical chart data were abstracted for a random sample of patients with each infection type (102 patients – IFI, 93 patients – MRSA pneumonia, and 87 patients—MRSA cSSTI). Descriptive analysis found that incidence of IFI (per 1000 hospital discharges) was higher than MRSA cSSTI and MRSA pneumonia (IFI: 1.95 and 2.57; MRSA cSSTI: 2.01 and 0.48; and MRSA pneumonia 0.59 and 0.55 for Saudi Arabia and Lebanon, respectively). Median time from hospital admission to diagnosis and from admission to initiation of active therapy were 6 and 7 days, respectively, in IFI patients; median time from admission to diagnosis was 2 days for both MRSA pneumonia and cSSTI, with a median of 4 and 2 days from admission to MRSA-active antibiotic start, respectively. The mean hospital LOS was 32.4 days for IFI, 32.4 days for MRSA pneumonia and 26.3 days for MRSA cSSTI. Inpatient mortality was higher for IFI (42%) and MRSA pneumonia (30%) than for MRSA cSSTI (8%). At discharge, 33% of patients with IFI and 27% and 9% of patients with MRSA pneumonia and cSSTI, respectively, were considered to have failed therapy. In conclusion, there is a significant burden of these serious infections in the Middle East, as well as opportunity for hospitals to improve the delivery of patient care for difficult-to-treat infections by promoting expedited diagnosis and initiation of appropriate antimicrobial therapy.